2008
DOI: 10.1103/physrevb.77.205120
|View full text |Cite
|
Sign up to set email alerts
|

Inhomogeneous site charges at the boundary between the insulating, superconducting, and metallic phases ofβ-type bis-ethylenedithio-tetrathiafulvalene molecular charge-transfer salts

Abstract: We have examined time-averaged charges of the molecular donors around the phase boundary between the insulating, superconducting, and metal phases for ␤Љ-type ET ͓ET= bis-ethelenedithio-tetrathiafulvalene͔ salts with one ͑two͒ hole͑s͒ per two ͑three͒ molecules by using vibrational spectroscopy. Around the phase boundary, the site charges are neither those expected for a well-developed charge-ordered ͑CO͒ state nor a homogeneous distribution. The molecular charges exhibit an inhomogeneous distribution just abov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
44
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 41 publications
5
44
0
Order By: Relevance
“…From the angle dependence of the NMR spectra in the charge-ordered state, we found that below 8.5 K the site charge deviates strongly from the formal average value. This deviation is much larger than that observed below 100 K from Raman spectroscopy [18]. The NMR intensity ratio of charge-rich to charge-poor sites leads us to suggest a threefold charge pattern, which can be stabilized by the competition between off-site and on-site Coulomb interactions.…”
Section: −24mentioning
confidence: 67%
See 3 more Smart Citations
“…From the angle dependence of the NMR spectra in the charge-ordered state, we found that below 8.5 K the site charge deviates strongly from the formal average value. This deviation is much larger than that observed below 100 K from Raman spectroscopy [18]. The NMR intensity ratio of charge-rich to charge-poor sites leads us to suggest a threefold charge pattern, which can be stabilized by the competition between off-site and on-site Coulomb interactions.…”
Section: −24mentioning
confidence: 67%
“…As σ is directly related to ρ, different σ values between R and P sites confirm the modulation in the site charges. We see that in the low-temperature charge-ordered state the deviation from the formal charge is much larger than that observed between 10 and 100 K by Raman spectroscopy (ρ R − ρ P = 0.13e [18]). The NMR peak splitting due to this small charge disproportionation at high temperatures is probably concealed in the linewidth of our spectra (for the external field applied along the b axis).…”
Section: Fig 2 (Color Online)mentioning
confidence: 80%
See 2 more Smart Citations
“…Their insulating phase is likely to be the CO state. [7][8][9][10][11][12][13] Some of these salts exhibit superconductivity under applied or ambient pressure. 14,15 It has been suggested that the mechanism of superconductivity in these salts is intermediated not by antiferromagnetic fluctuations but by charge fluctuations.…”
Section: Introductionmentioning
confidence: 99%